Study of shear‐thickening and shear‐thinning behavior in rheology of self‐compacting concrete with micro‐nano bubble. (17th May 2022) - Yahyaei, Behnaz; Asadollahfardi, Gholamreza; Salehi, Amir Masoud; Esmaeili, Negar
Abstract: This research investigated the effect of using micro‐nano bubbles and superplasticizers on the rheology of self‐compacting concrete (SCC). Eight mix designs were made with different values of 4–5.5 kg/m 3 of superplasticizer. For comparison, half of the mix designs were made with micro‐nano bubbles, and the rest were made with tap water. Flowability, passing ability, and rheological tests were performed on all mixed designs. The results show that an increased rate of superplasticizer from 4 to 5 kg/m 3 improved flowability and passing ability in all specimens. The yield stress and plastic viscosity of SCC reduction were higher in samples made with micro‐nano bubbles. The shear‐thickening behavior was observed in SCC samples produced with tap water and the superplasticizer, and the c/μ (positive) ratio increased. While in SCC with micro‐nano bubbles, the shear‐thinning behavior was observed, and the c/μ (negative) ratio increased with increasing the superplasticizer dose.